Purification and Characterization of Catalase Enzymes from Chicken Liver and Sheep Erythrocytes - COBAN, ABDULKADIR; CIFTCI, MEHMET; OZDEMIR, HASAN; ALTIKAT, SAYIT (Asian Journal of Chemistry, 2010)
Catalase enzyme (H2O2: H2O2 oxidoreductase; E.C. 1.11.1.6) was purified from chicken liver and sheep erythrocytes, using DEAESephadex A50 ion exchange chromatography and some characteristics of the enzymes were investigated. The purification procedure was composed of 3 steps i.e., homogenate/hemolisate preparation, ammonium sulfate precipitation and DEAE-Sephadex A50 ion exchange chromatography. Chicken liver and sheep erythrocytes enzymes, having the specific activity of 560.46 and 1017.5 EU/mg proteins were purified with a yield of 30.06 and 22.23 %; 190.63 and 643.9-fold, respectively. In order to control the purification of enzymes were done, sodium dodecyl sulfate polyacrilamide gel electrophoresis (SDS-PAGE). SDS-PAGE showed a single band for each enzyme. Optimal pH, stable pH, optimal temperature, KM and Vmax values for H2O2 were also determined for the each enzyme. In addition, molecular weight and subunit molecular weights were found by SDS-PAGE and gel filtration chromatography respectively.